Development of Telemetry for Experimental Cryomedicine - Antonenko, Yevhenii O.; Chizh, Mykola O.; Buriak, Mykhailo M.; Osypenko, Oleksiy O. (Problems of Cryobiology and Cryomedicine, 2018)
Â Probl Cryobiol Cryomed 2018; 28(2): 161